Initial Complete Chloroplast Genomes of Alchemilla (Rosaceae): Comparative Analysis and Phylogenetic Relationships - Rono, Peninah Cheptoo; Dong, Xiang; Yang, Jia-Xin; Mutie, Fredrick Munyao; Oulo, Millicent A.; Malombe, Itambo; Kirika, Paul M.; Hu, Guang-Wan; Wang, Qing-Feng (Frontiers in Genetics, 2020)
The genus Alchemilla L., known for its medicinal and ornamental value, is widely distributed in the Holarctic regions with a few species found in Asia and Africa. Delimitation of species within Alchemilla is difficult due to hybridization, autonomous apomixes and polyploidy, necessitating efficient molecular based characterization. Herein, we report the initial complete chloroplast (cp) genomes of Alchemilla. The cp genomes of two African (Afromilla) species Alchemilla pedata and A. argyrophylla were sequenced, and phylogenetic and comparative analysis conducted in the family Rosaceae. The cp genomes mapped a typical circular quadripartite structure of lengths 152, 438 base pairs (bp) and 152,427 bp in A. pedata and A. argyrophylla, respectively. Alchemilla cp genomes were composed of a pair of inverted repeat (IRa/IRb) regions of length 25,923 bp and 25,915 bp, separating the small single copy (SSC) region of 17,980 bp and 17981 bp and a large single copy (LSC) region of 82,612 bp and 82,616 bp in A. pedata and A. argyrophylla, respectively. The cp genomes encoded 114 unique genes including 88 protein-coding genes, 37 tRNA genes and 4 rRNA genes. Additionally, 88 and 95 simple sequence repeats (SSR) and 37 and 40 tandem repeats were identified in A. pedata and A. argyrophylla, respectively. Significantly, the loss of group II intron in atpF gene and the presence of two pseudogenes (ycf1 and ycf68) were detected. Whole cp genome comparative analysis with eight other Rosaceae species showed high variation in five regions (trnK-UUU - rps16, trnV-UAC - atpB, atpA - atpF, rps12 - clpP, and rrn16 - trnV-GAV) located in the intergenic spacers. Phylogenetic analysis based on 26 whole cp genomes of Rosaceae species revealed a monophyletic clustering of Alchemilla nested within subfamily Rosoideae. Based on protein-coding region, negative selective pressure (Ka/Ks > 1) was detected. The availability of complete cp genome in the genus Alchemilla will contribute to species delineation and further phylogenetic and evolutionary studies in the family Rosaceae.